Influence of AI on Business Strategies of Music Culture Communication Companies - Fan, Guoxu (Transformations In Business & Economics, 2025)
The rise of AI has reshaped corporate strategies across different industries, including music culture communication companies (MCCCs) that specialise in generating, curating, and delivering music culture content. Using multivariate multiple linear regression (MMLR) analysis, this paper explores the impact of artificial intelligence (data analytics, machine learning algorithms, natural language processing, and automated production workflows) on the business strategies adopted by music culture communications companies in China, including music content creation, content curation, operational efficiency, audience engagement, and consumer personalisation. The study findings indicate that various AI tools have a significant impact on a wide range of business strategies of MCCCs. This research contributes to the extant studies by offering a nuanced understanding of how AI can be strategically incorporated within the MCCCs. The insights derived from this study provide the best practices for practitioners and researcher to guide them in improving corporate strategies to effectively navigate the complex digital domain. This study emphasises the significance of integrating AI to complement the sustainable growth of business strategies in MCCCs.